HUBUNGAN KONDISI FISIK RUMAH NELAYAN DENGAN KELUHAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI LINGKUNGAN PINTU ANGIN KELURAHAN SIBOLGA HILIR KECAMATAN SIBOLGA UTARA KOTA SIBOLGA TAHUN 2013 - Juni Ettha Hutapea; evi naria; devi santi (Lingkungan dan Kesehatan Kerja, 2014)
The relationship between the physical condition of fisherman’s house with Acute Respiratory Infection complaints on children under five years old in Lingkungan Pintu Angin Kelurahan Sibolga Hilir Kecamatan Sibolga Utara Kota Sibolga in 2013. Acute Respiratory Infection has been a serious health problem problems in Indonesia. According to the preliminary survey at the Puskesmas Pintu Angin, Acute Respiratory Infection takes the high number firstly out the data ten the most disease. Children under five years old very susceptible to respiratory infection. One of the causes Acute Respiratory Infection is physical condition of house is bad. The houses of fisherman in Lingkungan Pintu Angin area mostly in stage constructed above sea water and non permanent. The type of research is descriptive analytic study, with cross sectional design. Populations are all mothers with children under five years old and have house with a constructed stage that has been built above sea water, that is 74 people and sample is total sampling. The results showed that there was significant relationship between the natural lighting (p=0.015) and humidity (p=0.026) with complaints of Acute Respiratory Infections on child under five years old, while ventilation (p=0.07), floor (p=0.613), wall (p=0.322), and ceiling (p=0.119) there was no relationship. People who live in Lingkungan Pintu Angin, expected to open their windows every day and encourage them to keep cleanness their home. And education needs to be improved by public health officials about the healthy condition of the house, especially to prevent acute respiratory infection diseases. Keywords : House physical condition, Child under five years old, Acute Respiratory Infection